Investigation of the emotional effect on serving motivation clashes in university volleyball players - Xie, G.; Lu, X.; Zhang, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Failure of athletes on the court can easily create poor moods including low spirits, passivity, and anxiety. These can in turn affect the input, coding and retrieval of information. This study aimed to investigate the consistency of emotional effect on motivation clashes of university varsity volleyball players. Methods 144 university varsity volleyball players participated in the study. A 2×2×4 experimental design was used, where Variable 1 (during testing) is motivational type, composed of light mood and sad mood; and variable 2 (within testing) refers to the result of matches, including wins and losses; and the third variable is the serving schema used. Results The results demonstrated that the average degree to which the forced choice of schema A, B, C or D was agreed upon was 4.26, 4.28, 2.80, 3.17, respectively. There was difference in volleyball players` resolve in the case of clashes between pursuit and avoidance at serving. Through 2×2×4 analysis of the experiment of three mixing factors, the following result could be revealed that mood type (during test) or factor A had a significant effect (P<0.05); match type (within test) factor B had no significant effect (P>0.05); and the serving schema, (within test) factor C had significant effect (P<0.01); the interactive effect between match type, mood type and problematic situation was not significant [(factor ABC), P>0.05]. Conclusions Most players approved that attacking power should be emphasized simultaneously with the reduction of misplay at serving or advocated the reduction of misplay with stable attacking power. Most players also disapproved of serving regardless of misplays. The emotion of athletes poses a potential risk for volleyball serving. Athletes with high spirits are more motivated to evade and to seek evasion compared with the athletes with a sad mood.